International Monetary Fund Annual Report 2007 : Making the Global Economy Work for All. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 2008)
The 2007 Annual Report to the Board of Governors reviews the IMF's activities and policies during the financial year (May 1, 2006, through April 30, 2007). This year's Report has been streamlined and translated into three more languages than in the past: Arabic, Japanese, and Russian. Besides an Overview, the chapters cover promoting financial and macroeconomic stability and growth through surveillance; program support; capacity building: technical assistance and training; and the IMF's governance, organization, and finances. The full financial statements for the year and other appendixes are provided on a CD-ROM. ISSN 0250-7498.